2023
DOI: 10.1111/sltb.13017
|View full text |Cite
|
Sign up to set email alerts
|

How do explicit, implicit, and sociodemographic measures relate to concurrent suicidal ideation? A comparative machine learning approach

René Freichel,
Sercan Kahveci,
Brian O’Shea

Abstract: IntroductionSuicide is a leading cause of death, and decades of research have identified a range of risk factors, including demographics, past self‐injury and suicide attempts, and explicit suicide cognitions. More recently, implicit self‐harm and suicide cognitions have been proposed as risk factors for the prospective prediction of suicidal behavior. However, most studies have examined these implicit and explicit risk factors in isolation, and little is known about their combined effects and interactions in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Specifically, the Attitude IAT−behavior intention and Stereotype IAT−behavior intention p-values were 0.172 and 0.739, respectively. Finally, Freichel et al (2023) employed several machine learning methods to access the usefulness of implicit suicide cognitions, self-harm IATs, to predict concurrent desire to self-harm or die with an online community sample of 6,855 participants. Specifically, they assessed whether self-harm IATs add to the prediction capability of (explicit) concurrent self-reported suicidality (thoughts or ideas about the possibility of ending one's life) and desire to self-harm, over and above more easily collected measures -such as sociodemographic factors, self-reported history of self-harm and suicide, and explicit momentary self-harm and suicide cognitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the Attitude IAT−behavior intention and Stereotype IAT−behavior intention p-values were 0.172 and 0.739, respectively. Finally, Freichel et al (2023) employed several machine learning methods to access the usefulness of implicit suicide cognitions, self-harm IATs, to predict concurrent desire to self-harm or die with an online community sample of 6,855 participants. Specifically, they assessed whether self-harm IATs add to the prediction capability of (explicit) concurrent self-reported suicidality (thoughts or ideas about the possibility of ending one's life) and desire to self-harm, over and above more easily collected measures -such as sociodemographic factors, self-reported history of self-harm and suicide, and explicit momentary self-harm and suicide cognitions.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they assessed whether self-harm IATs add to the prediction capability of (explicit) concurrent self-reported suicidality (thoughts or ideas about the possibility of ending one's life) and desire to self-harm, over and above more easily collected measures -such as sociodemographic factors, self-reported history of self-harm and suicide, and explicit momentary self-harm and suicide cognitions. Freichel et al (2023) observed that, in their best-performing model, self-harm, suicide, and death IATs offered very little (<2%) and often no predictive value on top of explicit measures that are much easier to collect to explain concurrent self-reported suicidality. Mood, explicit associations, and past suicidal thoughts and behaviors were the most important predictors of concurrent self-reported suicidality.…”
Section: Discussionmentioning
confidence: 99%
“…They assessed whether self-harm IATs add to the prediction capability of (explicit) concurrent self-reported suicidality (thoughts or ideas about the possibility of ending one's life) and desire to self-harm, over and above more easily collected measuressuch as sociodemographic factors, self-reported history of self-harm and suicide, and explicit momentary self-harm and suicide cognitions. Freichel et al (2023) observed that, in their best-performing model, self-harm, suicide, and death IATs offered very little (less than 2%) and often no predictive value on top of explicit measures that are much easier to collect to explain concurrent self-reported suicidality. Mood, explicit associations, and past suicidal thoughts and behaviors were the most important predictors of concurrent self-reported suicidality.…”
Section: Several Comments On Tablementioning
confidence: 99%